Global Economic Prospects, January 2015 : Having Fiscal Space and Using It - World Bank Group (Washington, DC, 2014)
Global growth again disappointed in 2014 but a lackluster recovery is underway, with increasingly divergent prospects in major economies. Looking ahead, growth is expected to rise slowly, supported by continued recovery in high-income countries and receding domestic headwinds in developing economies. Weak global trade growth and lower commodity prices are projected to persist while financial conditions will likely tighten gradually. Risks to the outlook are still tilted to the downside.